THE INFLUENCE OF MARKET ORIENTATION, ENTREPRENEURSHIP ORIENTATION, BUSINESS STRATEGY, AND INNOVATION ON THE PERFORMANCE - Angelina, Angelina; Handoyo, Sarwo Edy (Graduate Program of Universitas Tarumanagara, 2024)
This examination aims to investigate the influence of market orientation, entrepreneurial orientation, commercial enterprise method, and innovation on the commercial enterprise performance of SMEs within the production sector in North Jakarta. The pattern selection approach in this study used a non-probability sampling technique with a convenience sampling technique. The sample on this look at is a convection business in North Jakarta with a complete of 100 respondents. data have analyzed the usage of the SEM technique with the SmartPLS utility. The consequences of this have a look at located that there may be a fine and significant effect of marketplace orientation on business performance, entrepreneurial orientation has an effective and good-sized impact on commercial enterprise overall performance, commercial enterprise method has an advantageous and vast effect on commercial enterprise performance, innovation has an insignificant high-quality effect on business performance.